Perikanan Tangkap Ramah Lingkungan Ikan Cakalang di Teluk Tomini - Syamsuddin, Syamsuddin; Salam, Aziz (The NIKe Journal, 2023)
This research aims to analyze environmental friendly fishing technoligies of skipjack tuna (Katsuwonus pelamis Linneus) fishery. This research was conducted from April to Juni 2022 in Teluk Tomini Sea, Gorontalo Province. Data collected by surveys, observations, interviews and questionnaire. Environmental friendly aspects were analyzed with function of values provided by Monintja (2000) and Mallawa, et.al. (2019). Result shows that fishing technologies such as drag line, hand-line, purse-seine, and payang (mini purse-seine) are consecutively environmentally friendly.